Strategi Manajemen Humas dalam Menaikkan Jumlah Siswa di SMP Negeri 6 Satap Baraka - Alda; Muh. Ardiansyah; Sumarlin Mus (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This research examines Public Relations Management Strategies to Increase the Number of Students at SMP Negeri 6 Satap Baraka. The study focuses on how public relations management strategies enhance student enrollment at SMP Negeri 6 Satap Baraka, including supportive and inhibiting factors affecting the implementation of these strategies. The approach used is qualitative with a descriptive analysis. Data sources include the school principal, vice principal, PR team, committee, and the community. Data collection methods consist of interviews, observations, and documentation. Data analysis techniques involve data collection, data reduction, data display, and conclusion drawing. The results of this study indicate that public relations management strategies to increase student enrollment at SMP Negeri 6 Satap Baraka include: 1) Operational Strategies such as the PR team having specific efforts or mechanisms to manage PR programs involving the community and school committee; 2) Persuasive and Educational Strategies including distributing brochures containing the school's vision, mission, and advantages, as well as conducting socialization to emphasize the importance of education for children; 3) Social Responsibility Strategies like door-to-door visits to maintain relationships between the school and the community, and participating in community and institutional activities; 4) Collaboration Strategies involving partnerships with local health centers and participating in community work activities; 5) Supporting factors such as community support and maintaining harmonious relationships fostering good school credibility; 6) Inhibiting factors such as inadequate road infrastructure and the majority of parents being farmers, making it difficult to reach them. The triggering factor discouraging enrollment in this school is the presence of more competitive schools with larger student bodies and an Islamic environment.